A historical overview of the activity of the Trade Union of Healthcare Workers in Poland in the years 1946-1981 - Przybek-Mita, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2016)
In the interwar period in Poland there was no trade union bringing together all healthcare workers. Medical personnel belonged to various professional organisations and trade unions, representing the entire profession or only selected parts of it. This situation, according to state authorities, resulted in competitive actions, which led to the struggle for a better professional position and the improvement of working conditions and pay only for their own professional group. The analysis of the situation before the war gave birth to the idea of establishing an organisation of representatives of all groups of healthcare professionals: doctors, dentists, pharmacists, nurses, midwives, medical analysts, teachers of the medical profession and others. On 26 August 1946, the Central Committee of Trade Unions appointed the Organising Committee of the Trade Union of Healthcare Workers. The Committee’s task was to form a union. The First National Congress of Delegates of Healthcare Workers was held on 1 - 2 December 1946 in Warsaw. The purpose of this study is to present the activities of the Trade Union of Healthcare Workers, with particular emphasis on the activities of the Section of Nurses. The analysis includes the activity of the Trade Union in the years 1946 - 1981, which was carried out through the following problem commissions: the economic commission, the social commission, the working women commission, the pensioners’ commission, the youth commission, the sport and tourism commission, the culture and education commission, the work protection commission and the historical commission.